Performance Appraisal of Tehran Firefighting Stations in Attempted and Threating Suicide with National and Global Standards (The First 6 Months of 2018) - Esmaeil Sadri Damirchi; Afrasyab Kheirdast; Andrej M Grjibovski; Eslamali Khodabandehlou; Saeed Pireinaladin (Tehran University of Medical Sciences, 2022)
Background: We aimed to compare the performance of Tehran firefighting stations in the incidents of suicide attempt and threats among Tehran citizens using international standards. Methods:  A research method was a descriptive-analytical study based on library studies. The data were analyzed by descriptive and inferential methods such as single group t-test and independent t-test. The statistical population of this study included all citizens in 22 districts of Tehran City that committed or threated to commit suicide in the 2018 year. They were selected in a targeted manner. All data were extracted and analyzed through the fire department in the first half of 2018 in the action and threat of suicide. Results: Men commit suicide more than women do. Moreover, the average time of exit from station and the average travel time are shorter than Iranian and world standards. The people saved by firefighters outnumber the people who died in suicide, which indicates the satisfactory performance of firefighters in relief and rescue operations. In suicide operations, according to the general results obtained from statistical calculations of departure time from the station and the average travel time, which are the two main factors in evaluating the performance of firefighters in suicide accidents, which in comparison with international standards. It was significantly lower and the performance of firefighters was positive. Conclusion: The average duration of exit from station and the average travel time, are significantly lower than international standards, which demonstrates the good performance of firefighters.